Essential emergency imaging - Lewiss, Resa E.; Saul, Turandot; Shah, Kaushal (Essential emergency medicine series, 2012)
"Part of the Essential Emergency Medicine Series, this book offers emergency department staff a one-stop shop for information about all aspects of imaging. With the demand for cost-effective treatment, and the plethora of imaging options, the emergency physician needs to know which test will provide the best information with the least impact on the patient. The authors present information in a systematic, user-friendly approach. Beginning with the suspected diagnosis, the clinician reviews a brief overview of the condition, usual findings, and possible lab tests. "Bedside Pearls" reflect usual findings; classic images with more pearls about the specific technique follow. Each chapter ends with the advantages and disadvantages of the various imaging modalities."-- Provided by publisher